The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/jcpe.12815
|View full text |Cite
|
Sign up to set email alerts
|

One‐piece zirconia oral implants for single‐tooth replacement: Three‐year results from a long‐term prospective cohort study

Abstract: Aim: This 3-year report of a prospective long-term cohort investigation aimed to evaluate the clinical and radiographic outcomes of a one-piece zirconia oral implant for single-tooth replacement. Materials and Methods:Sixty-five patients received a 1-stage implant surgery with immediate temporization. Standardized radiographs were taken at implant insertion, after 1 year, and after 3 years to monitor peri-implant bone levels. A univariate analysis of the association of different baseline parameters on marginal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…34 In the peri-implant mucosa of zirconia ceramic implants, zirconia elements have been detected as well, however the origin and influence of metal or ceramic ions or particles on peri-implantitis remains unclear. 17 Furthermore, the host-response and interaction between lymphocyte-and monocyte-macrophage lineage as well as the influence of nano-and microparticles on the microbial biofilm and cytokine release in peri-implant inflammation is not elucidated and future studies could shed more light on the etiological discussion. 9 Within this study, the first histological comparison of human peri-implantitis lesions around ceramic and titanium implants was performed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…34 In the peri-implant mucosa of zirconia ceramic implants, zirconia elements have been detected as well, however the origin and influence of metal or ceramic ions or particles on peri-implantitis remains unclear. 17 Furthermore, the host-response and interaction between lymphocyte-and monocyte-macrophage lineage as well as the influence of nano-and microparticles on the microbial biofilm and cytokine release in peri-implant inflammation is not elucidated and future studies could shed more light on the etiological discussion. 9 Within this study, the first histological comparison of human peri-implantitis lesions around ceramic and titanium implants was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Influence of metal particles and ions on peri‐implant biofilm and their possible role in the development, formation and production of extracellular polysaccharides is discussed in current research 34 . In the peri‐implant mucosa of zirconia ceramic implants, zirconia elements have been detected as well, however the origin and influence of metal or ceramic ions or particles on peri‐implantitis remains unclear 17 . Furthermore, the host‐response and interaction between lymphocyte‐ and monocyte‐macrophage lineage as well as the influence of nano‐ and microparticles on the microbial biofilm and cytokine release in peri‐implant inflammation is not elucidated and future studies could shed more light on the etiological discussion 9 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have confirmed stable peri‐implant bone levels around zirconia implants (Kniha et al, ; Pieralli, Kohal, Jung, et al, ). For specific zirconia implants, however, marginal bone loss was remarkably high (Kohal, Schwindling, Bächle, & Spies, ; Kohal, Spies, Bauer, & Butz, ). Early detection of bone lesions around implants is, therefore, as important for zirconia implants as it is for titanium implants.…”
Section: Introductionmentioning
confidence: 99%